Molecular Dynamic Simulation of Centella asiatica Compound as an Inhibitor of Advanced Glycation End Products - Lili Legiawati, Fadilah Fadilah, Kusmarinah Bramono, Siti Setiati, Em Yunir (Journal of Applied Pharmaceutical Science, 2020)
The studies have suggested that advanced glycation end products (AGEs) induce stress oxidative and inflammatory pathway, which results in chronic complication. Centella asiatica (CA) has been shown as a promising candidate for AGE inhibitor due to its ability of reducing AGE production. This study aims to explore the molecular docking of CA active compound as an inhibitor of AGEs and receptor AGEs (RAGEs). The top three docking structures were picked for molecular dynamic (MD) simulations. Based on MD simulation in this study, we found that CA active compound had been proven to interact with AGEs and RAGE. AGEs bound to asiaticoside, madasiatic acid, and madecassic acid with a binding energy of −11.8253, −10.6724, and −10.1462 kcal/mol, respectively. Nonetheless, Asn106, Asp324, Asp376, Tyr420, and Tyr500 of AGEs made a significant contribution to the complex of asiaticoside AGE, as well as those for the madasiatic acid AGE, which were Asn118 and Tyr500. RAGE bound to asiaticoside, asiatic acid, and isothankunik acid with a binding energy of −10.6125, −9.4469, and −9.1015 kcal/mol, respectively. CA active compounds, specifically asiatic acid, madasiatic acid, and madecassic acid, interacted with AGEs, whereas asiaticoside and isothankunik acid interacted with RAGE based on docking and model studies.
Keywords: In silico, Centella asiatica, AGEs, RAGE.